Promoting transformative learning through formative assessment in higher education - Chan Yuen Fook; Gurnam Kaur Sidhu (Penerbit Universiti Kebangsaan Malaysia, 2013)
This paper presents a discussion on the advancement of transformative learning through formative assessment in higher education and why researchers believe this concept of formative assessment and transformative learning hold so much promise as an inclusive approach in higher education. The researchers of this study conducted a survey in a Malaysian public university to examine the perceptions of lecturers, undergraduates and postgraduates as on how formative assessment can enhance the development of transformative learning using a self-regulated and student-focused assessment model. In this study, researchers identified the impact of formative assessment on transformative learning in higher education. Based on the study conducted, the researchers also present a model of sustainable assessment that emphasizes how formative assessment can facilitate transformative learning in higher education. This formative oriented assessment model proposes a meaningful and student-oriented learning environment for effective self-regulatory learning among students. The researchers hope this study will fulfill a need in higher education for both practical and theoretical information for experts in a wide array of tertiary education settings.